Fullerene derivatives and n-type semiconductor materials
By further refining the fullerene derivatives, the purity of their 99% is improved, and the problem of low photoelectric conversion efficiency of fullerene derivatives outside PCBM in the prior art is solved, and high-efficiency photoelectric conversion of n-type semiconductor materials is achieved.
Patent Information
- Application Number
- CN202010288942.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2013-09-02
- Filing Date
- 2014-05-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2034-05-16
AI Technical Summary
In the prior art, fullerene derivatives other than PCBM have not yet achieved stable and good photoelectric conversion efficiency, and their application in the development of new n-type semiconductor materials is limited by the position and number of substituent introductions.
By further purifying the fullerene derivatives refined by GPC in Patent Document 3, especially using HPLC analysis and elemental analysis to confirm the improvement of purity, fullerene derivatives with a purity of more than 99% were prepared for use as n-type semiconductor materials.
The photoelectric conversion efficiency has been significantly improved, proving that further refining fullerene derivatives can achieve performance improvements in n-type semiconductor materials.
Smart Images

Figure CN111471007B_ABST
Abstract
Description
[0001] This case is filed on May 16, 2014 、Application No. 201480028347.5(PCT / JP2014 / 063126) , a divisional application of a patent application entitled “Fullerene derivatives and n-type semiconductor materials”. Technical Field
[0002] The present invention relates to fullerene derivatives and n-type semiconductor materials. Background Art
[0003] Organic thin-film solar cells are formed by coating solutions using organic compounds as photoelectric conversion materials, and have the following advantages: 1) low cost for equipment production; 2) easy to manufacture on a large scale; 3) flexible and can be used in a wide range of locations compared to inorganic materials such as silicon; 4) less concern about resource depletion, etc. Therefore, in recent years, the development of organic thin-film solar cells has been carried out, and in particular, the use of bulk heterojunction structures can significantly improve the photoelectric conversion efficiency, which has attracted widespread attention.
[0004] Among the materials for photoelectric conversion elements used in organic thin-film solar cells, poly-3-hexylthiophene (P3HT) is known as an organic p-type semiconductor material with excellent performance for p-type semiconductors. Recently, in order to obtain higher functions, compounds with structures that can absorb a wide range of wavelengths of sunlight and structures that adjust energy levels (donor-acceptor type π-conjugated polymers) have been developed, which have greatly contributed to the improvement of performance. Examples of such compounds include poly(p-phenylene vinylene) and poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]] (PTB7).
[0005] On the other hand, fullerene derivatives are also actively studied for n-type semiconductors, and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) has been reported as a material with excellent photoelectric conversion performance (see Patent Documents 1 and 2 described below). However, there are almost no examples of fullerene derivatives other than PCBM that have been proven to achieve stable and good photoelectric conversion efficiency.
[0006] In recent years, fullerene derivatives for organic solar cells other than PCBM have been reported. However, these are comparisons in special device configurations after removing the current collecting material of the anode (ITO electrode) (non-patent document 1), and have almost the same performance as PCBM (non-patent document 2). In addition, the disubstituted derivatives reported by Y. Li et al. (non-patent document 3), as reported by ETHoke et al., P3TH achieved a conversion efficiency higher than PCBM, but the donor-acceptor type π-conjugated polymer can only obtain a low conversion efficiency (non-patent document 4).
[0007] Thus, a highly functional n-type material other than PCBM that is not limited to p-type materials and can achieve high conversion efficiency has not been known so far.
[0008] Several synthesis methods have been proposed for fullerene derivatives. From the perspective of yield and purity, a method for synthesizing a fullerene derivative having a three-membered ring portion obtained by using a diazo compound and a method for synthesizing a fullerene derivative having a five-membered ring portion obtained by adding a methyleneamine ylide produced from a glycine derivative and an aldehyde are known as excellent methods.
[0009] The PCBM is a fullerene derivative having a three-membered ring portion, and is obtained by obtaining a mixture of three products obtained by adding a carbene intermediate to a fullerene skeleton, and then undergoing a conversion reaction using light irradiation or heat treatment. However, the derivative of the three-membered ring portion obtained by this production method has limitations on the position and number of substituents introduced, and therefore, there are major constraints in the development of new n-type semiconductors.
[0010] On the other hand, fullerene derivatives having a 5-membered ring portion are considered to be excellent in terms of structural diversity, but there are almost no reports of fullerene derivatives having excellent performance as n-type semiconductor materials for organic thin-film solar cells. As one of the few examples thereof, the fullerene derivatives described in Patent Document 3 described later can be cited.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2009-8426
[0014] Patent Document 2: Japanese Patent Application Publication No. 2010-92964
[0015] Patent Document 3: Japanese Patent Application Publication No. 2012-089538
[0016] Non-patent literature
[0017] Non-patent document 1: T. Itoh et al., Journal of Materials Chemistry, 2010, Vol. 20, p. 9226
[0018] Non-patent document 2: T. Ohno et al., Tetrahedron, 2010, Vol. 66, p. 7316
[0019] Non-patent document 3: Y. Li et al., Journal of American Chemical Society, 2010, Vol. 132, p. 1377
[0020] Non-patent document 4: ETHoke et al., Advanced Energy Materials, 2013, Vol. 3, p. 220 Summary of the invention
[0021] Problems to be solved by the invention
[0022] According to Patent Document 3, the fullerene derivative described therein exhibits high photoelectric conversion efficiency, but further improvement of the photoelectric conversion efficiency is desired.
[0023] That is, a main object of the present invention is to provide a material having excellent performance as an n-type semiconductor, particularly as an n-type semiconductor for a photoelectric conversion element such as an organic thin-film solar cell.
[0024] Methods for solving problems
[0025] Each fullerene derivative in the examples of Patent Document 3 was purified by preparative GPC and therefore can be presumed to have high purity. In fact, the results of HPCL analysis conducted by the inventors of the present invention show that the fullerene derivatives are basically pure.
[0026] Therefore, it is considered that further improvement in photoelectric conversion efficiency cannot be expected even if these fullerene derivatives are further purified.
[0027] However, surprisingly, it was found that the photoelectric conversion efficiency can be significantly improved by further refining the fullerene derivative represented by the following formula (1) among the fullerene derivatives purified by preparative GPC in the examples of Patent Document 3. It was not clear by HPLC whether the purity was improved by the further purification, but it was confirmed by elemental analysis that the purity was improved to a certain extent.
[0028] Formula (1):
[0029]
[0030] [wherein, ring A represents C 60Fullerenes;
[0031] R 1 represents an alkyl group which may have one or more substituents or an aryl group which may have one or more substituents; and
[0032] Ar represents an aryl group which may be substituted with one or more alkyl groups.]
[0033] The inventors of the present invention have further conducted intensive studies based on the above findings and have completed the present invention.
[0034] Therefore, the present invention includes the following aspects and the like.
[0035] Item 1.
[0036] An n-type semiconductor material comprising a fullerene derivative represented by formula (1) having a purity of 99% or more as defined below,
[0037] Formula (1):
[0038]
[0039] [wherein, ring A represents C 60 Fullerenes;
[0040] R 1 represents an alkyl group which may have one or more substituents or an aryl group which may have one or more substituents; and
[0041] Ar represents an aryl group which may be substituted with one or more alkyl groups.]
[0042] The above purity is set to the maximum value of the absolute value of the difference between the analysis value of the elemental analysis of carbon and the theoretical value, the absolute value of the difference between the analysis value of the elemental analysis of hydrogen and the theoretical value, and the absolute value of the difference between the analysis value of the elemental analysis of nitrogen and the theoretical value. max (%), is defined by the following formula:
[0043] Purity (%) = 100-D max (%)
[0044] Item 2.
[0045] The n-type semiconductor material as described in item 1 is used for an organic thin film solar cell.
[0046] Item 3.
[0047] An organic power generation layer comprising the n-type semiconductor material and the p-type semiconductor material described in item 2.
[0048] Item 4.
[0049] An organic power generation layer as described in any one of items 1 to 3, wherein the p-type semiconductor material is composed of a donor-acceptor type π-conjugated polymer having benzodithiophene, dithiophene-silole or N-alkylcarbazole as a donor unit and benzothiadiazole, thienothiophene or thiophenepyrroledione as an acceptor unit.
[0050] Item 5.
[0051] The organic power generation layer as described in item 4, wherein the above-mentioned donor-acceptor type π-conjugated polymer is poly(thieno[3,4-b]thiophene-co-benzo[1,2-b:4,5-b']thiophene) or poly(dithieno[1,2-b:4,5-b'][3,2-b:2',3'-d]silole-alt-(2,1,3-benzothiadiazole).
[0052] Item 6.
[0053] The organic power generation layer according to item 4, wherein the donor-acceptor type π-conjugated polymer is poly(thieno[3,4-b]thiophene-co-benzo[1,2-b:4,5-b′]thiophene).
[0054] Item 7.
[0055] An organic power generation layer as described in any one of items 1 to 6, wherein the p-type semiconductor material is poly-3-hexylthiophene or poly [[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]].
[0056] Item 8.
[0057] The organic power generation layer according to any one of items 1 to 7, further comprising diiodooctane.
[0058] Item 9.
[0059] A photoelectric conversion element comprising the organic power generation layer according to any one of items 3 to 8.
[0060] Item 10.
[0061] The photoelectric conversion element according to item 9, which is an organic thin-film solar cell.
[0062] Item 11.
[0063] The n-type semiconductor material as described in item 1 is used for a photosensor array.
[0064] Item 12.
[0065] The photoelectric conversion element according to item 9, which is a photosensor array.
[0066] Item 1A.
[0067] An n-type semiconductor material comprising a fullerene derivative represented by formula (1A) having a purity of 99% or more as defined below,
[0068] Formula (1A):
[0069]
[0070] [wherein, ring A represents C 60 Fullerenes.]
[0071] The above purity is set to the maximum value of the absolute value of the difference between the analysis value of the elemental analysis of carbon and the theoretical value, the absolute value of the difference between the analysis value of the elemental analysis of hydrogen and the theoretical value, and the absolute value of the difference between the analysis value of the elemental analysis of nitrogen and the theoretical value. max (%), is defined by the following formula:
[0072] Purity (%) = 100-D max (%)
[0073] Item 2A.
[0074] The n-type semiconductor material as described in item 1A is used for an organic thin film solar cell.
[0075] Item 3A.
[0076] An organic power generation layer comprising the n-type semiconductor material and the p-type semiconductor material described in item 2A.
[0077] Item 4A.
[0078] An organic power generation layer as described in any one of items 1A to 3A, wherein the p-type semiconductor material is composed of a donor-acceptor type π-conjugated polymer having benzodithiophene, dithiophene-silole or N-alkylcarbazole as a donor unit and benzothiadiazole, thienothiophene or thiophenepyrroledione as an acceptor unit.
[0079] Item 5A.
[0080] An organic power generation layer as described in item 4A, wherein the above-mentioned donor-acceptor type π-conjugated polymer is poly(thieno[3,4-b]thiophene-co-benzo[1,2-b:4,5-b']thiophene) or poly(dithieno[1,2-b:4,5-b'][3,2-b:2',3'-d]silole-alt-(2,1,3-benzothiadiazole).
[0081] Item 6A.
[0082] The organic power generation layer as described in item 4A, wherein the donor-acceptor type π-conjugated polymer is poly(thieno[3,4-b]thiophene-co-benzo[1,2-b:4,5-b′]thiophene).
[0083] Item 7A.
[0084] An organic power generation layer as described in any one of items 1A to 6A, wherein the p-type semiconductor material is poly-3-hexylthiophene or poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]].
[0085] Item 8A.
[0086] The organic power generation layer according to any one of items 1A to 7A, further comprising diiodooctane.
[0087] Item 9A.
[0088] A photoelectric conversion element comprising the organic power generation layer according to any one of items 3A to 8A.
[0089] Item 10A.
[0090] The photoelectric conversion element as described in Item 9A, which is an organic thin-film solar cell.
[0091] Item 11A.
[0092] The n-type semiconductor material as described in item 1A is used in a photosensor array.
[0093] Item 12A.
[0094] The photoelectric conversion element as described in Item 9A is a photosensor array.
[0095] Effects of the Invention
[0096] The n-type semiconductor material of the present invention is particularly useful as an n-type semiconductor for a photoelectric conversion element such as an organic thin-film solar cell, and can achieve high photoelectric conversion efficiency. DETAILED DESCRIPTION
[0097] Hereinafter, the n-type semiconductor material and the like of the present invention will be described in detail.
[0098] n-type semiconductor material
[0099] The n-type semiconductor material of the present invention is an n-type semiconductor material comprising a fullerene derivative represented by formula (1) defined below having a purity of 99% or more.
[0100] Formula (1):
[0101]
[0102] [wherein, ring A represents C 60 Fullerenes;
[0103] R 1 represents an alkyl group which may have one or more substituents or an aryl group which may have one or more substituents; and
[0104] Ar represents an aryl group which may be substituted with one or more alkyl groups.]
[0105] Therefore, the n-type semiconductor material of the present invention can be an n-type semiconductor material containing the fullerene derivative represented by formula (1) at a purity of 99% or more as defined above.
[0106] In the present specification, examples of the “alkyl group” include alkyl groups having 1 to 8 carbon atoms (preferably 1 to 6 carbon atoms), such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, neopentyl, 1-ethylpropyl, hexyl, isohexyl, 1,1-dimethylbutyl, 2,2-dimethylbutyl, 3,3-dimethylbutyl and 2-ethylbutyl.
[0107] In the present specification, examples of the “aryl group” include aryl groups having 6 to 14 carbon atoms, such as phenyl, 1-naphthyl, 2-naphthyl, 2-biphenylyl, 3-biphenylyl, 4-biphenylyl and 2-anthryl.
[0108] As R 1 Examples of the substituent of the "alkyl group which may have one or more substituents" include an alkoxy group, an alkoxycarbonyl group, and a polyether group.
[0109] The number of the substituent is preferably one.
[0110] In the present specification, examples of "alkoxy" include those of the formula: R a -O-(where R a represents an alkyl group.
[0111] In the present specification, examples of the "alkoxycarbonyl group" include a group consisting of: R a -O-CO-(where R a represents an alkyl group.
[0112] In this specification, examples of the polyether group include the following: a -(OR b ) n -O-, where R a and R bThe same or different, representing an alkyl group (R b Each time it occurs, it may be the same or different. ), and n represents an integer of 1 to 4.
[0113] As R 1 Examples of the substituent of the "aryl group which may have one or more substituents" include a halogen atom.
[0114] In the present specification, examples of the "halogen atom" include fluorine, chlorine, bromine and iodine.
[0115] The number of the substituent is preferably 0 (no substitution) to 2.
[0116] R 1 The "aryl group which may have one or more substituents" is preferably a phenyl group which may be substituted with one or two fluorine atoms.
[0117] Ar is preferably a phenyl group which may be substituted with one alkyl group, and more preferably a phenyl group.
[0118] The fullerene derivative represented by the formula (1) is preferably, for example, a fullerene derivative represented by the formula (1A), a fullerene derivative represented by the formula (1B), or a fullerene derivative represented by the formula (1C).
[0119] Formula (1A):
[0120]
[0121] [wherein, ring A represents C 60 Fullerenes.]
[0122] Formula (1B):
[0123]
[0124] [wherein, ring A represents C 60 Fullerenes.]
[0125] Formula (1C):
[0126]
[0127] [wherein, ring A represents C 60 Fullerenes.]
[0128] The purity is preferably 99.0% or more, more preferably 99.1% or more, even more preferably 99.2% or more, even more preferably 99.3% or more, particularly preferably 99.4% or more, 99.5% or more, 99.6% or more, or 99.7% or more.
[0129] The above purity is set to the maximum value of the absolute value of the difference between the analysis value of the elemental analysis of carbon and the theoretical value, the absolute value of the difference between the analysis value of the elemental analysis of hydrogen and the theoretical value, and the absolute value of the difference between the analysis value of the elemental analysis of nitrogen and the theoretical value. max (%), is defined by the following formula:
[0130] Purity (%) = 100-D max (%)
[0131] In addition, "%" used in element analysis means mass percentage.
[0132] That is, the absolute values of the differences between the analyzed values and the theoretical values of carbon, hydrogen, and nitrogen in the elemental analysis are respectively set as D carbon , D hydrogen and D nitrogen When, for example, among these, D carbon When the value of D is maximum, max D carbon At this time, the purity (%) is calculated by the following formula:
[0133] Purity (%) = 100-D carbon (%)
[0134] In the present specification, C represented by ring A may be referred to as 60 Fullerenes are represented as is often done in the art by the following structural formula:
[0135]
[0136] In addition, sometimes C 60 Fullerene is abbreviated as C60.
[0137] That is, for example, the fullerene derivative shown in the above (1) can be represented by the following formula (1'):
[0138]
[0139] The fullerene derivative represented by the above formula (1) has good solubility in various organic solvents, and therefore a thin film containing the fullerene derivative can be easily formed by a coating method.
[0140] Furthermore, when the fullerene derivative represented by the above formula (1) is used as an n-type semiconductor material together with an organic p-type semiconductor material to prepare an organic power generation layer, a bulk heterojunction structure can be easily formed.
[0141] Method for producing fullerene derivative (1)
[0142] The fullerene derivative represented by the above formula (1) can be synthesized by, for example, the synthesis method described in the above Patent Document 3 or a method based thereon.
[0143] Specifically, the fullerene derivative represented by the above formula (1) can be synthesized, for example, by the method shown in the figure below.
[0144]
[0145] (In this specification, Ph in the chemical formula represents a phenyl group.)
[0146] <Process A>
[0147] In step A, N-substituted glycine (compound (b)) is reacted with an aldehyde (compound (a)) and C 60 The fullerene (compound (c)) is reacted to obtain a fullerene derivative represented by formula (1) (compound (1)).
[0148] Aldehyde (compound (a)), N-substituted glycine (compound (b)) and C 60 The amount ratio of fullerene (compound (c)) is arbitrary, but from the viewpoint of improving the yield, it is usually 1: 60 The aldehyde compound (compound (a)) and N-substituted glycine (compound (b)) are each used in an amount of 0.1 to 10 mol, preferably 0.5 to 2 mol, per 1 mol of the fullerene (compound (c)).
[0149] The reaction is carried out in the absence of a solvent or in a solvent. Examples of the solvent include carbon disulfide, chloroform, ethylene dichloride, toluene, xylene, chlorobenzene, dichlorobenzene, etc. These solvents can be mixed in an appropriate ratio. As the solvent, chloroform, toluene or chlorobenzene, o-dichlorobenzene, bromobenzene, etc. are preferred, and toluene, chlorobenzene, etc. are particularly preferred.
[0150] The reaction temperature is usually in the range of room temperature to about 150° C., preferably in the range of about 80 to about 120° C. In the present specification, room temperature is in the range of 15 to 30° C.
[0151] The reaction time is generally in the range of about 1 hour to about 4 days, preferably in the range of about 10 to about 24 hours.
[0152] The reaction is preferably carried out under reflux with stirring.
[0153] The aldehyde (compound (a)), N-substituted glycine (compound (b)) and C 60 Fullerene (compound (c)) is a known compound and can be synthesized by a known method (for example, the method described in Patent Document 3) or a method based thereon, or can be purchased commercially.
[0154] The compound (1) obtained in step A is purified to a purity as defined above of 99% or more (preferably 99.0% or more, more preferably 99.1% or more, even more preferably 99.2% or more, even more preferably 99.3% or more, particularly preferably 99.4% or more).
[0155] This purification can be carried out by a conventional purification method.
[0156] Specifically, for example, the purification can be carried out by the following method.
[0157] For example, the obtained compound (1) is purified by silica gel column chromatography (as a developing solvent, for example, preferably hexane-chloroform, hexane-toluene or hexane-carbon disulfide), and then further purified by HPLC (preparative GPC) (as a developing solvent, for example, preferably chloroform or toluene, particularly preferably chloroform).
[0158] The purified compound (1) is further purified by washing with a solvent and recrystallizing.
[0159] In the solvent washing, the solid of the above-mentioned refined compound (1) is preferably washed with different solvents for more than two times. The washing, for example, is carried out by collecting the solid of the above-mentioned refined compound (1) in a container such as an eggplant-shaped flask and performing the washing in a conventional manner. The two or more washings preferably include washing with a solvent having a relatively high polarity (for example, methanol and acetone) and washing with a solvent having a relatively low polarity (for example, tetrahydrofuran (THF) and hexane). In order to reduce the residual solvent, the solvent washing is preferably first carried out with a solvent washing with a high polarity. Specifically, the solvent washing is particularly preferably carried out by washing with methanol, acetone, dichloromethane, tetrahydrofuran (THF) and hexane in sequence.
[0160] Recrystallization is preferably carried out, for example, from hexane-chlorobenzene or hexane-carbon disulfide.
[0161] It is also effective to use a HPLC column for fullerene separation in combination with the solvent washing and recrystallization purification method, or as another method. The HPLC column for fullerene separation can be purchased commercially, and as an example, COSMOSIL Buckyprep series (Nacalai tesque company) can be cited. The column purification can also be carried out more than 2 times as needed.
[0162] Examples of the solvent used for purification using an HPLC column dedicated to fullerene separation include one or more selected from toluene, chloroform, and the like.
[0163] The solvent is removed from the compound (1) further purified in this manner. The solvent is preferably removed by removing the solvent in the supernatant, then removing the solvent remaining in the solid of the compound (1) by evaporation, and further heating and drying (e.g., drying at 60 to 100° C. for 8 to 24 hours) under reduced pressure (e.g., 10 mmHg or less, more preferably 1 mmHg or less).
[0164] Application of n-type semiconductor materials
[0165] The n-type semiconductor material of the present invention can be preferably used as an n-type semiconductor material for a photoelectric conversion element such as an organic thin-film solar cell.
[0166] The n-type semiconductor material of the present invention is usually used in combination with an organic p-type semiconductor material (organic p-type semiconductor compound).
[0167] Examples of the organic p-type semiconductor material include poly-3-hexylthiophene (P3HT), poly-p-phenylene vinylene, poly-alkoxy-p-phenylene vinylene, poly-9,9-dialkylfluorene, and poly-p-phenylene vinylene.
[0168] There are many research examples of these as solar cells, and they are easily available, so devices with stable performance can be easily obtained.
[0169] In order to obtain higher conversion efficiency, a donor-acceptor type π-conjugated polymer capable of absorbing long-wavelength light by narrowing the band gap (low band gap) is effective.
[0170] These donor-acceptor type π-conjugated polymers have a donor unit and an acceptor unit, and have a structure in which these units are alternately arranged.
[0171] Examples of the donor unit used therein include benzodithiophene, dithienosilole, and N-alkylcarbazole, and examples of the acceptor unit include benzothiadiazole, thienothiophene, and thienylpyrroledione.
[0172] Specifically, polymer compounds such as poly(thieno[3,4-b]thiophene-co-benzo[1,2-b:4,5-b']thiophene) (PTBx series) and poly(dithieno[1,2-b:4,5-b'][3,2-b:2',3'-d]silole-alt-(2,1,3-benzothiadiazole) series in which these units are combined can be mentioned.
[0173] Among these, preferred examples include
[0174] (1) poly({4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl}{3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl}) (PTB7, the structural formula is shown below),
[0175] (2) poly[(4,8-di(2-ethylhexyloxy)benzo[1,2-b:4,5-b']dithiophene)-2,6-diyl-alt-((5-octylthieno[3,4-c]pyrrole-4,6-dione)-1,3-diyl) (PBDTTPD, the structural formula is shown below),
[0176] (3) poly[(4,4'-bis(2-ethylhexyl)dithieno[3,2-b:2',3'-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl] (PSBTBT, the structural formula is shown below),
[0177] (4) poly[N-9″-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT, structural formula shown below) and
[0178] (5) Poly[1-(6-{4,8-bis[(2-ethylhexyl)oxy]-6-methylbenzo[1,2-b:4,5-b′]dithiophen-2-yl}{3-fluoro-4-methylthieno[3,4-b]thiophen-2-yl}-1-octanone) (PBDTTT-CF, structural formula shown below) and the like.
[0179] Among them, more preferred examples include PTB-based compounds having a fluorine atom at the 3-position of thieno[3,4-b]thiophene as an acceptor unit, and particularly preferred examples include PBDTTT-CF and PTB7.
[0180]
[0181] (In the formula, n represents the number of repetitions.)
[0182]
[0183] (In the formula, n represents the number of repetitions.)
[0184]
[0185] (In the formula, n represents the number of repetitions.)
[0186]
[0187] (In the formula, n represents the number of repetitions.)
[0188]
[0189] (In the formula, n represents the number of repetitions.)
[0190] The organic power generation layer prepared by combining the n-type semiconductor material of the present invention with the above-mentioned organic p-type semiconductor material (for example, preferably P3HT or donor-acceptor type π-conjugated polymer material, for example, more preferably PTB series such as PTB7) can show higher conversion efficiency than when using existing n-type semiconductor materials composed of fullerene derivatives represented by PCBM.
[0191] The n-type semiconductor material of the present invention has good solubility in various organic solvents. Therefore, an organic power generation layer can be prepared by a coating method, and a large-area organic power generation layer can be easily prepared.
[0192] In addition, the n-type semiconductor material of the present invention has good compatibility with the organic p-type semiconductor material and has moderate self-aggregation. Therefore, the fullerene derivative is used as an n-type semiconductor material (organic n-type semiconductor material) to easily form an organic power generation layer of a bulk heterojunction structure. By using the organic power generation layer, an organic thin film solar cell or light sensor with high conversion efficiency can be obtained.
[0193] The n-type semiconductor material of the present invention is preferably used alone as an n-type semiconductor material, and may also be used in combination with other n-type semiconductor materials. That is, the n-type semiconductor material of the present invention may also be used as a mixture of the n-type semiconductor material of the present invention and other n-type semiconductor materials. It goes without saying that the use of such a combination or mixture is also the use of the n-type semiconductor material of the present invention.
[0194] Therefore, by using it as the n-type semiconductor material of the present invention, an organic thin-film solar cell having excellent performance can be produced at low cost.
[0195] In addition, as another application of the organic power generation layer containing (or consisting of) the n-type semiconductor material of the present invention, there is an image sensor for a digital camera. In response to the requirement for high functionality (high precision) of digital cameras, the problem of low sensitivity has been pointed out for image sensors composed of existing silicon semiconductors. In contrast, it is expected that high sensitivity and high precision can be achieved by using image sensors composed of organic materials with high light sensitivity. For the material of the light receiving part of such a sensor, it is required to absorb light with high sensitivity and thereby efficiently generate electrical signals. In response to such a requirement, the organic power generation layer containing (or consisting of) the n-type semiconductor material of the present invention can efficiently convert visible light into electrical energy, and therefore, as the material of the light receiving part of the above-mentioned image sensor, it can exhibit high functionality.
[0196] Organic power generation layer
[0197] The organic power generation layer of the present invention contains the n-type semiconductor material and the p-type semiconductor material of the present invention.
[0198] The organic power generation layer of the present invention is preferably composed of the n-type semiconductor material and the p-type semiconductor material of the present invention.
[0199] The organic power generation layer of the present invention can be a light conversion layer (photoelectric conversion layer).
[0200] In the organic power generation layer of the present invention, it is preferred that the n-type semiconductor material of the present invention and the above-mentioned organic p-type semiconductor material form a bulk heterojunction structure.
[0201] In the thin film formation of the organic power generation layer, the n-type semiconductor material of the present invention has good compatibility with the organic p-type semiconductor material (preferably P3HT or donor-acceptor type π-conjugated polymer material) and has moderate self-aggregation. Therefore, according to the present invention, an organic power generation layer containing the n-type semiconductor material of the present invention and the organic p-type semiconductor material and having a bulk heterojunction structure can be easily obtained.
[0202] The organic power generation layer of the present invention further contains diiodooctane or octanedithiol. Thus, the organic power generation layer of the present invention has a high photoelectric conversion efficiency. As described later, this is believed to be due to the fact that the n-type semiconductor material of the present invention and the above-mentioned organic p-type semiconductor material form a bulk heterojunction structure, but the present invention is not limited thereto.
[0203] The organic power generation layer of the present invention can be prepared, for example, by the following operation: dissolving the n-type semiconductor material of the present invention and the above-mentioned organic p-type semiconductor material in an organic solvent (which may contain additives), and forming a thin film on a substrate from the obtained solution using a known thin film forming method such as spin coating, casting, dipping, inkjet and screen printing.
[0204] The main component of the organic solvent (that is, the component that serves as a solvent other than the additives described below) is, for example, one or more selected from chloroform, toluene, and chlorobenzene.
[0205] The above organic solvent preferably contains diiodooctane or octanedithiol as an additive. Thus, an organic power generation layer with higher photoelectric conversion efficiency can be formed. This is believed to be due to the fact that the n-type semiconductor material of the present invention and the above organic p-type semiconductor material form a bulk heterojunction structure. The content of diiodooctane or octanedithiol in the above organic solvent is usually 1 to 5% (v / v), preferably 2 to 4% (v / v), and particularly preferably 3% (v / v).
[0206] In order to form an effective bulk heterojunction structure in an organic power generation layer containing an n-type semiconductor and a p-type semiconductor, annealing is sometimes performed after the organic thin film is formed. In particular, when P3HT, poly(p-phenylene vinylene), poly-alkoxy-p-phenylene vinylene, poly-9,9-dialkylfluorene, poly(p-phenylene vinylene), etc. are used as p-type semiconductor materials, for example, by annealing at 80 to 130°C for about 10 to 30 minutes, the conversion efficiency can be improved.
[0207] On the other hand, when a donor-acceptor type π-conjugated polymer such as PTB7 is used as a p-type semiconductor material, annealing is not required.
[0208] Organic thin film solar cells
[0209] The organic thin-film solar cell of the present invention includes the organic power generation layer of the present invention described above.
[0210] Therefore, the organic thin film solar cell of the present invention has high photoelectric conversion efficiency.
[0211] The structure of the organic thin-film solar cell is not particularly limited and can be the same structure as a known organic thin-film solar cell. The organic thin-film solar cell of the present invention can be manufactured according to a known method for manufacturing an organic thin-film solar cell.
[0212] As an example of an organic thin film solar cell containing the fullerene derivative, for example, a solar cell having a structure in which a transparent electrode (anode), an anode-side charge transport layer, an organic power generation layer, a cathode-side charge transport layer and a counter electrode (cathode) are sequentially stacked on a substrate can be exemplified. The organic power generation layer is preferably a semiconductor thin film layer (i.e., a photoelectric conversion layer) having a bulk heterojunction structure containing an organic p-type semiconductor material and a fullerene derivative of the present invention as an n-type semiconductor material. In a solar cell of such a structure, as materials for each layer other than the organic power generation layer, known materials can be appropriately used. Specifically, as materials for electrodes, for example, aluminum, gold, silver, copper, and indium oxide (ITO) can be cited. As materials for the charge transport layer, for example, PEDOT:PSS (poly (3,4-ethylenedioxythiophene): poly (4-styrenesulfonic acid)) can be cited.
[0213] Light Sensor
[0214] As described above, the photoelectric conversion layer obtained in the present invention effectively functions as a light receiving part for an image sensor in a high-function product of a digital camera. Compared with the existing light sensor using a silicon photodiode, it can be seen that overexposure (flared highlights) does not occur in bright places, and a clear picture can be obtained in dark places. Therefore, a higher-quality picture than that of existing cameras can be obtained. The light sensor is constructed by a light receiving part composed of a silicon substrate, an electrode, a photoelectric conversion layer, a color filter, and a microlens. The thickness of the light receiving part can be about several 100nm, which can be composed of a fraction of the thickness of an existing silicon photodiode.
[0215] Example
[0216] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited thereto.
[0217] Symbols and abbreviations in the examples are used in the following meanings. In addition, in this specification, symbols and abbreviations commonly used in the technical field to which the present invention belongs are used.
[0218] s: Single peak
[0219] bs: broad singlet
[0220] d: Twin Peaks
[0221] dd: double doublet
[0222] t: triplet
[0223] m: multiple peaks
[0224] Preparation Example 1 (Compound 1)
[0225] The fullerene derivative (Compound 1) was synthesized by the following reaction formula.
[0226]
[0227] C 60 Fullerene (175 mg, 0.25 mmol), benzaldehyde (27 mg, 0.25 mmol) and N-phenylglycine (76 mg, 0.5 mmol) were stirred in toluene (100 mL) under reflux for 24 hours. After cooling, the solvent was distilled off, and the product was separated by silica gel column chromatography (n-hexane: toluene = 20: 1 to 10: 1), and further purified by preparative GPC (chloroform) to obtain sample 1-1 of compound 1. The yield was 29.7%.
[0228] The structure of the obtained compound was confirmed by nuclear magnetic resonance (NMR): JEOL JNM-ECS400 model (400 MHz) and mass spectrometry (MS): JEOL JMS-700 model (FAB: Matrix-NBA).
[0229] 1 H-NMR (CDCl3): δ5.00 (1H, d, J = 10.5Hz), 5.68 (1H, d, J = 10.5Hz), 6.08 (1H, s), 7.02-7.10 (1H, m), 7.22-7.40 (7H, m), 7.70-7.81 (2H, m).
[0230] MS(FAB+): m / z 916(M+H).HRMS calcd for C74H13N 915.1048; found 915.1039.
[0231] Sample 1-1 was washed with an organic solvent and recrystallized as described below to obtain Sample 1-2 having improved purity.
[0232] Sample 1-1 was collected in an eggplant-shaped flask, washed with methanol, acetone, dichloromethane, THF and hexane in sequence, and then recrystallized from hexane-chlorobenzene.
[0233] After the supernatant solvent was removed, the solvent remaining in the obtained solid was evaporated, and the solid was further reduced in pressure (1 mmHg) using a vacuum pump and dried in a thermostatic bath at 80° C. for 15 hours to obtain Sample 1-2.
[0234] Preparation Example 2 (Compound 2)
[0235]
[0236] Heptanal (28.5 mg, 0.25 mmol), N-phenylglycine (76 mg, 0.5 mmol) and C 60 Fullerene (175 mg, 0.25 mmol) was stirred in 100 ml of toluene at 110°C for 24 hours. After cooling, the solvent was distilled off and the reactant was separated by column chromatography (SiO2, n-hexane: toluene = 10:1) to obtain compound 2 (163 mg, 70.6%), which was further purified by preparative GPC (chloroform) to obtain sample 2-1 of compound 2.
[0237] 1H-NMR (CDCl3) δ: 0.88 (3H, t, J = 6.9Hz), 1.25-1.40 (4H, m), 1.40-1.60 (2H ,m),1.72-1.86(2H,m),2.40-2.52(1H,m),2.58-2.70(1H,m),5.09(1H,d ,J=10.5Hz), 5.39(1H,d,J=10.5Hz), 5.66(1H,dd,J=7.8,5.0Hz), 7.00(1H,dd,J=7.3,7.3Hz), 7.30(2H,d,J=7.3Hz), 7.45(2H,dd,J=7.3,7.3Hz).
[0238] Sample 2-1 was further subjected to HPLC (column used: COSMOSIL Buckyprep (Nacalai Tesque Co., Ltd.; solvent: toluene) was purified. The sample obtained here was washed with an organic solvent and recrystallized as follows to obtain a sample 2-2 with improved purity.
[0239] Sample 2-1 was collected in an eggplant-shaped flask, washed with methanol, acetone, dichloromethane, THF and hexane in sequence, and then recrystallized from hexane-chlorobenzene.
[0240] After the supernatant solvent was removed, the solvent remaining in the obtained solid was evaporated, and the solid was further reduced in pressure (1 mmHg) using a vacuum pump and dried in a thermostatic bath at 80° C. for 15 hours to obtain a sample 2-2.
[0241] Preparation Example 3 (Compound 3)
[0242]
[0243] (1) Synthesis process of 2,5,8-trioxadecanal
[0244] According to the method described in Journal of Organic Chemistry, Vol. 61, 1996, p. 9070, 2,5,8-trioxadecanal was synthesized by the following method.
[0245] First, a vinyl chloride solution (15 mL) of dimethyl sulfoxide (DMSO) (5 mL) was added dropwise to a vinyl chloride solution (75 mL) of oxalyl chloride (3 mL) at -78°C. 2,5,8-trioxadecanol (5 mL) and a vinyl chloride solution (30 mL) were added thereto at -78°C, and triethylamine (20 mL) was further added at the same temperature. After stirring for 30 minutes, the mixture was stirred at room temperature for 15 hours. The solvent was distilled off, and the reactant was separated by silica gel column chromatography (eluent CH2Cl2:EtOH=10:1) to obtain 2,5,8-trioxadecanal.
[0246] 1 H-NMR(CDCl3): δ3.34(3H,s),3.45-3.75(8H,m),4.16(2H,bs),9.80(1H,s).
[0247] (2) Synthesis process of compound 3
[0248] N-phenylglycine (76 mg, 0.5 mmol), C 60 Fullerene (360 mg, 0.5 mmol) and 2,5,8-trioxadecanal (324 mg, 0.5 mmol) synthesized by the above method were stirred in chlorobenzene (200 mL) at 120°C for 72 hours. After cooling, the solvent was distilled off, and the product was separated by silica gel column chromatography (toluene: ethyl acetate = 50: 1) to obtain 194 mg of compound 3 (yield 40.0%), which was further purified by preparative GPC (chloroform) to obtain sample 3-1 of compound 3.
[0249] 1 H-NMR (CDCl3): δ3.34 (3H, s), 3.45-3.76 (8H, m), 4.40 (1H, dd, J = 10.3, 2.8 Hz), 4.59 (1H, dd, J = 10.3, 6.2 Hz), 5. 30(2H,s),5.84(1H,d,J=6.2,2.8Hz), 7.01(1H,t,J=7.7Hz), 7.28(2H,d,J=8.0Hz), 7.47(2H,dd,J=8.0,7.7Hz).
[0250] Sample 3-1 was further purified by HPLC (column: COSMOSIL Buckyprep (Nacalaitesque Company; solvent: toluene) was purified. The obtained sample was washed with an organic solvent and recrystallized as follows to obtain a sample 3-2 with improved purity.
[0251] Sample 3-1 was collected in an eggplant-shaped flask, washed with methanol, acetone, dichloromethane, THF and hexane in sequence, and then recrystallized from hexane-chlorobenzene.
[0252] After the supernatant solvent was removed, the solvent remaining in the obtained solid was evaporated, and the solid was further reduced in pressure (1 mmHg) using a vacuum pump and dried in a thermostatic bath at 80° C. for 15 hours to obtain a sample 3-2.
[0253] Purity determination of compound 1 sample
[0254] The purity of Sample 1-1 (Comparative Example 1-1) and Sample 1-2 (Example 1-2) of Compound 1 was determined by elemental analysis.
[0255] Elemental Analysis Each sample was burned using an elemental analyzer, CHN-Corder MT6 (Yanaco), and the amount ratio of the resulting gases (CO2, H2O, and N2) was measured. The mass percentages of carbon, hydrogen, and nitrogen were calculated based on the obtained values.
[0256] <Molecular formula of compound 1> C 74 H 13 N
[0257] <Theoretical values of the mass percentages of carbon, hydrogen, and nitrogen (calculated by taking into account the isotope ratio)>
[0258] C: 97.04%; H: 1.43%; N: 1.53%
[0259] <Measured values of mass percentages of carbon, hydrogen and nitrogen>
[0260] C: 93.78%; H: 1.82%; N: 1.44%
[0261] For carbon, hydrogen, and nitrogen, the absolute value with the largest absolute value among the differences between the theoretical value and the measured value of elemental analysis is set as D. max (%), and the purity of the sample was calculated by the following formula.
[0262] Purity of sample (%) = 100-D max
[0263] The results are shown below.
[0264] Sample 1-1
[0265] The difference between the theoretical value and the measured value of carbon element analysis = -3.26%, D carbon =3.26%
[0266] The difference between the theoretical value and the measured value of hydrogen element analysis = +0.39%, Dhydrogen =0.39%
[0267] The difference between the theoretical value and the measured value of nitrogen element analysis = -0.09%, D nitrogen =0.09%D max =D carbon =3.26%
[0268] Purity: 97.0%
[0269] Sample 1-2
[0270] The difference between the theoretical value and the measured value of elemental analysis of carbon = -0.56%, D carbon =0.56%
[0271] The difference between the theoretical value and the measured value of hydrogen element analysis = +0.33%, D hydrogen =0.33%
[0272] The difference between the theoretical value and the measured value of nitrogen element analysis = +0.13%, D nitrogen =0.13%D max =D carbon =0.56%
[0273] Purity: 99.4%
[0274] Purity determination of samples of compounds 2 and 3
[0275] The purity of samples of Compound 2 (Sample 2-1 (Comparative Example 2-1) and Sample 2-2 (Example 2-2)) and samples of Compound 3 (Sample 3-1 (Comparative Example 3-1) and Sample 3-2 (Example 3-2)) was determined by elemental analysis in the same manner as the purity determination of the sample of Compound 1 described above.
[0276] The results are shown below.
[0277] Sample 2-1
[0278] The difference between the theoretical value and the measured value of carbon element analysis = -3.41%, D carbon =3.41%
[0279] The difference between the theoretical value and the measured value of hydrogen element analysis = +1.09%, D hydrogen =1.09%
[0280] The difference between the theoretical value and the measured value of nitrogen element analysis = +0.73%, D nitrogen =0.73%
[0281] D max =D carbon=3.41%
[0282] Purity: 96.6%
[0283] Sample 2-2
[0284] The difference between the theoretical value and the measured value of elemental analysis of carbon = +0.71%, D carbon =0.71%
[0285] The difference between the theoretical value and the measured value of hydrogen element analysis = +0.29%, D hydrogen =0.29%
[0286] The difference between the theoretical value and the measured value of nitrogen element analysis = +0.18%, D nitrogen =0.18%D max =D carbon =0.71%
[0287] Purity: 99.3%
[0288] Sample 3-1
[0289] The difference between the theoretical value and the measured value of carbon element analysis = -1.18%, D carbon =1.18%
[0290] The difference between the theoretical value and the measured value of hydrogen element analysis = +0.04%, D hydrogen =0.04%
[0291] The difference between the theoretical value and the measured value of nitrogen element analysis = +0.06%, D nitrogen =0.06%
[0292] D max =D carbon =1.18%
[0293] Purity: 98.8%
[0294] Sample 3-2
[0295] The difference between the theoretical value and the measured value of elemental analysis of carbon = +0.30%, D carbon =0.33%
[0296] The difference between the theoretical value and the measured value of hydrogen element analysis = +0.20%, D hydrogen =0.20%
[0297] The difference between the theoretical value and the measured value of nitrogen element analysis = +0.22%, D nitrogen =0.22%D max =D carbon=0.33%
[0298] Purity: 99.7%
[0299] For each sample, a solar cell was produced according to the following operation and performance evaluation was performed.
[0300] Performance Test Example 1
[0301] As an n-type semiconductor material, sample 1-1 or sample 1-2 obtained in the above-mentioned manufacturing example is used, as a p-type semiconductor material, P3HT (poly 3-hexylthiophene) or PTB7 is used, as a charge transport layer material, PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonic acid)) is used, and as electrodes, ITO (indium tin oxide) (anode) and aluminum (cathode) are used. An experimental solar cell is prepared by the method described below, and its performance is evaluated.
[0302] (1) Fabrication of experimental solar cells
[0303] A test solar cell was produced by the following operation.
[0304] 1) Pretreatment of substrate
[0305] An ITO patterned glass plate (manufactured by Sanrong Vacuum Co., Ltd.) was cleaned by ultrasonic wave with toluene, acetone, water and IPA (isopropyl alcohol) in this order for 15 minutes each.
[0306] Next, the ITO glass plate was placed in a UV ozone cleaning device (Filgen, UV253) and cleaned in the order of oxygen for 6 minutes, ozone for 30 minutes to 60 minutes, and nitrogen for 2 minutes.
[0307] 2) Preparation of PEDOT:PSS film
[0308] A PEDOT:PSS thin film as a charge transport layer was formed on the ITO glass plate pretreated in 1) above using a PEDOT:PSS mixed solution using an ABLE / ASS-301 type spin coating film forming apparatus.
[0309] The spin coating conditions were 500 rpm (5 seconds) and 3000 rpm (1 minute). The thickness of the formed PEDOT:PSS thin film was about 30 nm.
[0310] 3) Annealing
[0311] The ITO plate obtained in 2) above with the PEDOT:PSS thin film disposed on the surface was placed on a hot plate for annealing at 135° C. in an air atmosphere for 10 minutes and then cooled to room temperature.
[0312] 4) Fabrication of organic semiconductor films
[0313] Using a spin coating film forming device (manual spin coater) (MIKASA, MS-100), a solution of sample 1-1 or sample 1-2 containing pre-dissolved P3HT or PTB7 and compound 1, respectively, was spin coated on the above-mentioned PEDOT:PSS film (1200 rpm, 2 minutes) to obtain a laminate of an organic semiconductor thin film (light conversion layer) with a thickness of about 100 to 150 nm.
[0314] Chlorobenzene (diiodooctane added 3% (v / v)) was used as a solvent for the above solution.
[0315] 5) Vacuum evaporation of metal electrodes
[0316] Using a small high vacuum deposition apparatus (Eiko, VX-20), the laminate prepared in 4) was placed on a mask in the high vacuum deposition apparatus, and a 30 nm calcium layer and an 80 nm aluminum layer as a cathode were sequentially deposited.
[0317] (2) Measuring the current by simulating sunlight irradiation
[0318] When measuring the current by simulating sunlight irradiation, a source meter (Keithley, Model 2400), current and voltage measurement software, and a simulated sunlight irradiation device (Sanei Electric Manufacturing Co., Ltd., XES-301S) were used.
[0319] A certain amount of simulated sunlight was irradiated to each test solar cell produced in (1) above, the generated current and voltage were measured, and the energy conversion efficiency was calculated according to the following formula.
[0320] The measurement results of the short-circuit current, the open-circuit voltage, the fill factor (FF), and the conversion efficiency are shown in Table 1. The conversion efficiency is a value obtained by the following formula.
[0321] Conversion efficiency η(%)=FF(V oc ×J sc / P in )×100
[0322] FF: Curve Factor, V oc : Open voltage, J sc : Short-circuit current, P in : Incident light intensity (density)
[0323] [Table 1]
[0324]
[0325] As can be seen from Table 1, when the compound 1 with a purity of 99.4% is used, the conversion efficiency is significantly improved compared to when the compound 1 with a purity of 97% is used. In addition, in the combination with the compound 1 as an n-type semiconductor material, when PTB7 is used as a p-type semiconductor material, the conversion efficiency is significantly improved compared to when P3HT is used. In addition, when the compound 1 with a purity of 99.4% is used as the n-type semiconductor material and PTB7 is used as the p-type semiconductor material, extremely high conversion efficiency is obtained.
[0326] Performance Test Example 2
[0327] In the same manner as in Performance Test Example 1, using Sample 2-1 or Sample 2-2 obtained in Production Example 2 as the n-type semiconductor material, a test solar cell was produced and its performance was evaluated.
[0328] [Table 2]
[0329]
[0330] Performance Test Example 3
[0331] In the same manner as in Performance Test Example 1, using Sample 3-1 or Sample 3-2 obtained in Production Example 3 as the n-type semiconductor material, a test solar cell was produced and its performance was evaluated.
[0332] [Table 3]
[0333]
Claims
1. An organic power generation layer, characterized in that: Contains n-type semiconductor material and p-type semiconductor material, The n-type semiconductor material comprises a fullerene derivative represented by formula (1) having a purity of 99% or more, as defined below. Formula (1): In the formula, ring A represents C 60 Fullerenes; R 1 represents an alkyl group having 1 to 6 carbon atoms which may have one or more substituents or an aryl group having 6 to 14 carbon atoms which may have one or more substituents, wherein the substituent of the alkyl group having 1 to 6 carbon atoms which may have one or more substituents is of the formula R a -O- or R a -(OR b ) n -O-, the group represented by formula R a -O-, R a represents an alkyl group having 1 to 6 carbon atoms, the formula R a -(OR b ) n -O-, R a and R b are the same or different, and represent an alkyl group having 1 to 6 carbon atoms, R b In each occurrence, may be the same or different, and n represents an integer from 1 to 4; and Ar represents a phenyl group, The p-type semiconductor material is poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]], The purity is determined by setting the maximum value of the absolute value of the difference between the analysis value of elemental analysis of carbon and the theoretical value, the absolute value of the difference between the analysis value of elemental analysis of hydrogen and the theoretical value, and the absolute value of the difference between the analysis value of elemental analysis of nitrogen and the theoretical value to D. max (%), is defined by the following formula: Purity (%) = 100-D max (%).
2. The organic power generation layer according to claim 1, characterized in that: R 1 In the above-mentioned aryl group having 6 to 14 carbon atoms which may have one or more substituents, the substituent is a halogen atom.
3. The organic power generation layer according to claim 1 or 2, characterized in that: R 1 It is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 14 carbon atoms.
4. The organic power generation layer according to claim 1 or 2, characterized in that: It is used in organic thin-film solar cells.
5. The organic power generation layer according to claim 1 or 2, characterized in that: Also contains diiodooctane. 6 . A photoelectric conversion element comprising the organic power generation layer according to claim 1 .
7. The photoelectric conversion element according to claim 6, wherein: It is an organic thin film solar cell.
Citation Information
Patent Citations
Pressure sensor
JP2009008426A
Fullerene derivative
JP2010092964A
Purification of fullerene derivatives from various impurities
CN102459072A
Mixtures of fullerene derivatives and their use in electronic devices
JP2009542725A
Processing additives for manufacturing organic photocells
JP2011502363A